BIJI BUAH BISBUL (Diospyros blancoi) SEBAGAI BIOSORBEN Cr(III) - Nina Ariesta; Rifansyah Rifansyah; Dian Arrisujaya; Mamay Maslahat (Universitas Nusa Bangsa, 2018)
Velvet Apple Fruit Seeds (Diospyros blancoi) as Biosorbent of Cr(III) Velvet Apple Fruit (Diospyros blancoi) has not been explored more in Indonesia. The purpose of research was to explore the use of Velvet Apple Fruit seeds as adsobent of Cr(III) in waste. Biosorbent of velvet apple fruit seeds in removing Cr (III) metal ions has been investigated using batch method. Several parameters were used to determine absorption optimum conditions such as solution pH, contact time and biosorbent dosage. Langmuir, Freundlich and Temkin isotherm models were used in determining biosorption equilibrium. FTIR and SEM-EDX were used to characterize the velvet apple fruit seeds biosorbent. The equilibrium adsorption isotherms showed the velvet apple fruit seeds biosorbent had a maximum adsorption capacity of 5.592 mg/g. The adsorption efficiency of Cr (III) ion by velvet apple fruit seeds was 81.78%. The results showed that velvet apple fruit seeds potentially as an alternative low-cost biosorbent for removing heavy metal ions in solution.Keywords: biosorption, heavy metals, alternative biosorbent, waste water treatmentABSTRAK Buah bisbul di Indonesia belum tereksplor dengan baik potensinya. Tujuan penelitian adalah untuk megetahui potensi biji buah Bisbul sebagai adsorben logam Cr(III) pada limbah. Biosorben biji buah bisbul (Diospyros blancoi) dalam menyerap ion logam Cr(III) telah diteliti dengan menggunakan metode batch. Beberapa parameter digunakan untuk menentukan kondisi optimum penyerapan seperti pH larutan, waktu kontak dan dosis biosorben. Model isoterm Langmuir, Freundlich dan Temkin dipakai dalam menentukan kesetimbangan biosorpsi. FTIR dan SEM-EDX digunakan dalam mengkarakterisasi biosorben biji buah bisbul. Isoterm adsorpsi kesetimbangan menunjukkan biosorben biji buah bisbul mempunyai kapasitas adsorpsi maksimum 5,592 mg/g. Efisiensi penyerapan ion Cr(III) oleh biji buah bisbul mencapai 81,78%. Hasil penelitian menunjukkan bahwa biji buah bisbul berpotensi sebagai alternatif biosorben murah dalam menghilangkan ion logam berat dalam larutan.Kata kunci: biosorpsi, logam berat, alternatif biosorben, pengolahan air limbah